Normalizar la aparcería a través de un contrato en la ley orgánica de tierras rurales y territorios ancestrales - Guillén Ortega, Claudia Alejandra (2017)
With the enforcement of the Law on Rural Land, the former Agrarian Development Act was repealed, the first according to Art. 1 Regular "state relations with natural and legal, national and foreign, on land rural; and communes and communities, peoples and nationalities in the recognition and award gratuitously territories found in ancestral possession; and the protection and legal security of land ownership and territories ". Within this law as a way plots plots as a form of social organization and promotion of integration processes and regrouping of small plots is regulated. . To do so according to Article 65 of the Organic Law on Rural Land states: "It will speed the titling processes for the implementation of programs or plans for land productive integration of rural properties whose length is less than the Family Productive Unit developed by initiative and smallholder family farming, in accordance with this Law. "But the fact is that this problem is due to the increase of labor exploitation of the peasant sector by working on the farm because our country there is no sharecropping agreement very different contract plots governing land tenure in their favor in order that this social inequality is completed in the agricultural and livestock field that directly affects their families, because the excess effort and work does not allow them to live comfortably with his family family. Most of the available land, and above all the best land, are still in the hands of the dominant social groups, small farmers due to low capacity of capital accumulation and in some cases, by social structures established since colonial times have limited access to land and rural workers who do not possess they can only access this resource through indirect forms of tenure, most of the time, totally unfavorable conditions, the lack of such a contract kind. Sharecropping in Ecuador has been very important in the evolution of farms; moreover, much of the colonial and republican agrarian regime was based on evidence sharecropping relations Andean haciendas were characterized by different systems of sharecropping already by the type of crop, the type of products, the place of cultivation; system of sharecropping contract has apparently disappeared even laws do not consider, however it is something that is in force in the part of the saw in the indigenous sector and on the coast in the area of montubio, where landlords use this system of farm, because this contract system is a way of evading legal responsibilities to the worker.